Inculcation of employability skills in technical and vocational education: the knowledge of employability skills and teaching practices - Mat Sakam, Siti Zubaidah; Jamaluddin, Rahimah; Abdul Wahat, Nor Wahiza (Human Resource Management Academic Research Society, 2022)
Employability skills are a requirement for TVE graduates to be eligible for employment. Employers not only place academic approval requirements and technical skills but employers emphasize employability skills. It becomes more complicated as employers shift the responsibility for inculcating these employability skills to educational institutions. Inculcating employability skills by TVE teachers is eSENtial in producing human capital that will drive the nation's progress and sustainability. Therefore, this study examines the level of inculcation of employability skills and knowledge of employability skills among TVE teacher as well as the relationship between these two variables. This quantitative survey involved 199 TVE teachers from Special Education Secondary Schools, in Malaysia. The instrument were adapted from Ab Halim’s (2013); Ab Majid’s (2017);Osman and Basar’s (2015). The findings showed that the level of inculcating employability skills and TVE teacher’s employability skill knowledge were at high-level with mean scores 4.28 (SD=0.441) and 3.92 (SD=0.38) respectively. Based on pearson correlation analysis, findings indicated that teacher’s employability skill knowledge positively correlates with the inculcation of employability skills (r = 0.512, p .000). The findings indicated that when teachers’s employability skills knowledge is high or increases, this will also increase their behavior to inculcate employability skills among the students. This study gives the impression that teachers' knowledge of employability skills is very important for them to inculcate employability skills among the students. The findings of this study can be used as a reference by the Malaysian Ministry of Education in improving teaching competence among TVE educators. In addition, a continous teacher professional development training related to knowledge of employability skills should be provided to TVE teachers. It would be good if the Malaysian Ministry of Education could collaborate with stakeholders to get more information on employability skills required by employers and industries. With that, teachers can inculcate accurate employability skills among the students as preparation before they step out for employment. The further study uses a mixed method by adding elements of observation also interview is needed to handle the issue.